Peran Prosedur Operasional Standar dalam Meningkatkan Kepuasan Tamu di Restoran Palm Hotel Holiday Inn Resort Baruna Bali - Meriana, Ni Kadek; Nugraha, I Gede Putra (Universitas Pahlawan Tuanku Tambusai, 2025)
This study is a qualitative descriptive study conducted at the Palm Restaurant, Holiday Inn Resort Baruna Bali. The purpose of this study was to identify the role of standard operating procedures that have a major role in increasing guest satisfaction. This study was conducted for four months with data collection methods, namely interviews, observations and documentation, which were samples in the interview process were assistant managers and food and beverage supervisors at the Palm Restaurant. The results of this study indicate that the role of standard operating procedures in increasing guest satisfaction has reached 92% with service satisfaction, but is still not optimal. The implementation of standard operating procedures has not been optimal due to several factors including the level of self-awareness (personal) so that there is a figure of 8% for service dissatisfaction.